Konstruksi Aswaja An-Nahdliyah dalam Penguatan Kode Etik Akuntan - Prabowo, Muhammad Aras; Umam, Fuadul; Hidayani, Hidayani; Sugama, Alviansyah; Ummah, Rochmatul; Rahmat, Rahmat (AKTSAR: Jurnal Akuntansi Syariah, 2023)
The research aims to construct Aswaja An-Nahdliyah in the accountant's code of ethics to strengthen the ethics of the accounting profession. Using a literature review method, the analysis is enriched by sharing review literature sources according to the research topic. Researchers constructed an accountant's code of ethics that builds on the three pillars of Aswaja An-Nahdliyah: religious understanding, Manhajul fikr and Manhajul harakah. The results of the construction of the Aswaja An-Nahdliyah code of ethics are: as-shidqu, al-amanah wal wafa bil'ahd, al'ada, at-ta'awun and istiqomah and have characteristics based on spiritualism, nationalism and culture. The implementation of the Aswaja An-Nahdliyah accountant's code of ethics will give birth to Aswaja accountants, namely accountants who carry out their professional responsibilities on Islamic, Indonesian, cultural values and the accountant's code of ethics along with the rules that apply in the profession.